Carboxymethyl cellulose from sugar beet pulp cellulose as a hydrophilic polymer in coating of mandarin - Togrul, H; Arslan, N (Elsevier Sci Ltd, 2004)
Sugar beet pulp cellulose was converted carboxymethyl cellulose (CMC) by etherification. The coating of mandarin surfaces with films formed by different emulsions containing CMC from sugar beet pulp cellulose as a hydrophilic polymer was carried out. Paraffin wax, beeswax and soybean oil; CMC with degree of substitution of 0.6670; Emulgin PE, triethanolamine, oleic acid and sodium oleate were used as hydrophobic phases, hydrophilic polymer and emulsifying agents in the coating of mandarins to extend postharvest life and to maintain their quality, respectively. Mandarins were stored in a storage chamber at 25 degreesC and at a relative humidity of 75%. Samples were taken at regular intervals for analysis. The changes in weight loss, pH, soluble solids, titratable acidity and ascorbic acid of the coated samples with storage time were investigated in comparison with the uncoated samples to determine the delay in the deterioration time of the samples. The effect of CMC as a hydrophilic polymer in coating emulsions on weight loss, pH, soluble solids, titratable acidity and ascorbic acid was also studied. The modified drying models describing the storage time dependence of weight loss were fitted to the experimental data and the model parameters in the equations were determined by multiple regression analysis. The coatings contributed to a lower reduction in pH. The coatings decreased the soluble solids and titratable acidity loses in comparison to the uncoated mandarins. The coating of mandarins delayed ascorbic acid loss. It was possible to extend the storage period with lower weight loss until 27 days by coating mandarin surfaces with emulsions containing CMC from sugar beet pulp cellulose as a hydrophilic polymer. It was found that the emulsion prepared using the mixture of soybean oil, CMC, sodium oleate and water was suitable for the coating of mandarins. (C) 2003 Elsevier Ltd. All rights reserved.
Keywords: sugar beet pulp; cellulose; carboxymethyl cellulose; coating; mandarin